RESERVOIR FEATURES OF THE UPPER CARBON SEDIMENTS (RUNOVSHCHYNSKA AREA OF THE DNIEPER-DONETS BASIN) - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main objective of this article is to highlight the results of investigations of filtration capacity features of sandstones and argillites of the Upper Carbon rocks in Runovshchynska area of The Dnieper-Donets basin. The purpose of the research was to assess the promising rocks as possible hydrocarbon reservoirs. The following reservoir features of rock samples such as the open porosity factor, permeability coefficients and residual water saturation factor have been investigated. The correlation of rock density with their porosity was also studied. The porosity study was carried out in atmospheric and reservoir conditions by gas volumetric method and fluid saturation. The bulk density of dry rock samples varies from 2,122 kg/m3 to 2,615 kg/m3 (average 2318 kg/m3), saturated rocks – from 2265 to 2680 kg/m3 (average 2449 kg/m3), and the specific matrix density – from 2562 to 2786 kg/m3 (average 2650 kg/m3). The open porosity coefficient of the studied rocks, in case they were saturated with the synthetic brine, varies from 0.058 to 0.190 (mean 0.126), but if they were saturated with N2 it varies from 0.066 to 0.203 (mean 0.145). Detailed analysis of reservoir conditions modeling revealed that porosity coefficient varies from 0.038 to 0.175 (mean 0.110). Due to the closure of microcracks under rock loading reduced to reservoir conditions the porosity decreases in comparison with atmospheric conditions, which causes a relative decrease in the porosity coefficient from 4.5% to 13.8% (mean 9.0%) from atmospheric conditions to reservoir conditions. The permeability coefficient of rocks varies from 0.03 fm2 to 240.57 fm2 (mean 11.87 fm2). The residual water saturation factor of rocks varies from 0.02 to 0.89 (mean 0.36). The classification of the reservoir characteristics of the investigated samples by the permeability coefficients and residual water saturation factors has been fulfilled. The correlation analysis has allowed establishing a series of empirical relationships between the reservoir parameters of the studied rocks (density, porosity coefficient, permeability coefficient and residual water saturation factor). The results of complex petrophysical researches indicated that the promising oil-bearing intervals of the horizons G-6, G-7v, G-7n have, in general increased values of reservoir parameters.
Keywords: filtration-capacitive parameters; density; porosity; permeability; residual water saturation; correlation dependencies; sandstones; mudstones